2015
DOI: 10.1098/rsos.150505
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mimicry and emotional contagion in domestic dogs

Abstract: Emotional contagion is a basic form of empathy that makes individuals able to experience others’ emotions. In human and non-human primates, emotional contagion can be linked to facial mimicry, an automatic and fast response (less than 1 s) in which individuals involuntary mimic others’ expressions. Here, we tested whether body (play bow, PBOW) and facial (relaxed open-mouth, ROM) rapid mimicry is present in domestic dogs (Canis lupus familiaris) during dyadic intraspecific play. During their free playful inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 54 publications
4
116
1
1
Order By: Relevance
“…Mutual rear-ups occurred only once (once for the bower and partner) in dog puppies, and never in wolf puppies. Therefore, it is possible that the puppies were limited by their lack of bodily control or social experience to rear-up or align their behaviors with a partner, and that this behavior increases in frequency with age, or potentially as a function of a preferred play partner rather than a littermate [27,30,33]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutual rear-ups occurred only once (once for the bower and partner) in dog puppies, and never in wolf puppies. Therefore, it is possible that the puppies were limited by their lack of bodily control or social experience to rear-up or align their behaviors with a partner, and that this behavior increases in frequency with age, or potentially as a function of a preferred play partner rather than a littermate [27,30,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, play bows may help strengthen bonds between dogs that share common motivations. Palagi et al [27] found that during dyadic dog play, both the open mouth display and play bow often elicited the same behavior in the partner immediately afterward, thus suggesting that rapid mimicry may indicate shared positive emotions and facilitate behavioral coordination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rise in oxytocin appears to facilitate further social interaction, producing a positive feedback loop that is likely an important mechanism underlying social bond formation in dogs and other animals (Romero et al, 2014). Consistent with this view, Palagi et al (2015) reported that during intraspecific play, dogs with longer associations showed increased rapid mimicry of the play faces and play bows of their partners.…”
Section: Gentle Affiliationmentioning
confidence: 70%
“…In dogs, the exchange of affiliation with conspecifics triggered the release of oxytocin, a hormone associated with social bonding and positive emotions, and the release of oxytocin may, in turn, increase the motivation to maintain long-term affiliative bonds with particular individuals (Romero et al, 2014). Boissy et al (2007) proposed that play and affiliation are some of the best behavioural indicators of positive emotions in animals, and Palagi et al (2015) suggested that during play, rapid mimicry between partners promotes contagion of such positive emotions. Thus, dogs' tendencies to form friendships allow them to transcend differences in sex, age, size and rank to create relaxed, compatible partnerships that likely add to their quality of life.…”
Section: Friendship and Its Benefitsmentioning
confidence: 98%